The classification of offending and crime related problems: a functional perspective - Ward, Tony (Psychology, crime & law, 2019)
In this paper we argue that it is time to adopt a broader classification strategy in forensic and correctional contexts based on the goals associated with offending behaviour. First, we briefly discuss the various roles of classification in science and what constitutes a good classification system. Second, we critically examine current systems of classifying crime and individuals who commit it, concentrating on the use of offense types, levels of risk, and dynamic risk factors. Third, we propose that a forensic/correctional classification system based on functional categories or kinds of behaviour is more likely to result in meaningful descriptive categories, better explanations, and ultimately more effective treatment than our current systems do. We then outline the Functional Offending Behaviour Classification Framework drawing together ideas from evolutionary biology, cognitive neuroscience, psychopathology, disability research, and ethology. Finally, we illustrate the advantages of our functional classification framework in comparison to traditional ways of classifying crime and offending behaviour.